Extraction and Characterization of Cellulose Fibers from the Stem of Momordica Charantia. Issue 6 (3rd June 2022) - Khan, Anish; Raghunathan, Vijay; Singaravelu, D Lenin; Sanjay, M.R.; Siengchin, Suchart; Jawaid, Mohammad; Alamry, Khalid A.; Asiri, Abdullah M.
ABSTRACT: Recently, bio-based composites are the prominent material to replace several synthetic fiber-based composites because of their abundant availability, ecological, biodegradable, and sustainable properties. This study aims to examine the use of new natural fibers, which were extracted from the Momordica charantia plant stem as reinforcement in polymer composites. The results showed that the Momordica charantia fibers had c ellulose content (61.2 %), density (1339 ± 6.4 kg/m 3 ), fiber diameter (198 ± 3.9 µm). The thermal studies using thermogravimetric analysis revealed the degradation temperature as 339.1°C with a char residue of 21% at 600°C. The results of this work confirmed that the properties of the Momordica charantia plant stem fibers are suitable materials as a reinforcement for the development of the biocomposite for potential applications.